An effective technique to posterior resin composite restorations - Dekon, Stefan Fiuza de Carvalho [UNESP]; Pereira, Leonardo Viana [UNESP]; Zavanelli, Adriana Cristina [UNESP]; Goiato, Marcelo Coelho [UNESP]; Resende, Cristina do Amparo; Santos, Daniela Micheline dos [UNESP] (Jaypee Brothers Medical Publishing, 2011)
AIM: The aim of this study is to present a clinical case in which an occlusal matrix device was used in a patient who needed to restore a posterior tooth. MATERIAL AND METHODS: A direct duplicate occlusal appliance was used (biteperf) in a patient who needed an occlusal restoration in two posterior teeth. RESULTS: Using the matrix helps having fast and accurate reproduction of the original anatomical details of the occlusal surface. The final result surprised with the presented restoration in terms of esthetic quality, despite the simplicity of the technique. CONCLUSION: Posterior teeth with initial lesions were confined to the occlusal surface of anatomically complex or fissured anatomy with or without signs of proximal caries wich are ideal candidates for this technique. The overlying enamel surface must be relatively intact; lesions of hidden or occult caries. CLINICAL SIGNIFICANCE: The aesthetic and time-saving benefits of the occlusal device (biteperf) are immediately clear. The matrix allows the fast and accurate reproduction of the anatomic details of the original occlusal surface of the tooth. The professionals who lack an artistic penchant and marked manual ability will be able to carry out excellent posterior resin composite restorations.
Keywords: Composite resins; Dental occlusion; Esthetics Dental